Willingness To Pay for Improving The Quality of Public Transportation - Pujiati, Amin; Nihayah, Dyah Maya; Bowo, Prasetyo Ari; Prastiwi, Fifi Setyo (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
This study aims to know the magnitude of the estimated average value of willingness to pay service users BRT Trans Semarang to improve the service quality and to know the change of the desired service quality improvement from the users of BRT Trans Semarang. Quantitative descriptive research approach with Contingent Valuation Method (CVM) is used to analysis the data from 100 respondents. Sampling techniques are carried out by means of purposive random sampling. The finding shows that the magnitude of the average value of willingness to pay IDR. 4,000 and quality service that needs to be fixed are a convenient bus stop placement, more emphasis on user safety, timeliness the potential as well as the necessity to depart and the priority age of BRT users. Government can review back the tariff policy of BRT Trans Semarang set appropriate response from the respondents because the estimated average value of WTP can be the basic reference point for setting the rates and can improve the quality of service to make it more adequate so that users feel at ease when using the BRT Trans Semarang